PENGEMBANGAN MEDIA VIDEO PENDIDIKAN BUDAYA SUKU KAJANG SEBAGAI MUATAN LOKAL UNTUK MENINGKATKAN KARAKTER SISWA KELAS X SMA NEGERI 10 BULUKUMBA - Alwi, M.; Rosalyn Anwar, Citra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The purpose of this study is to produce valid and practical educational video media products for use in the learning process. This research is carried out using the type of research and development (R&D) to produce a product. This study aims to, 1) determine the level of media needs for cultural education video media of the Kajang tribe, 2) know how to design educational video media, 3) know the level of validity and practicality of educational video media. The product development model used, namely the ADDIE Model in Husni (2018) consists of several stages, namely: Analysis, Design, Development, Implementation, and Evaluation. This model is suitable for developing interactive media because this model specifically discusses each component described in detail. The data collection techniques used are Qualitative Descriptive Analysis and Qualitative Descriptive Analysis. The subjects in this study were 2 validators consisting of media experts and content or material experts, class X students totaling 34 students and 1 teacher response. The validation results show that the educational video media products developed are declared to be of good qualification.